Effect of Irrigation Regimes and Nitrogen Levels on Growth and Yield of Cotton Genotypes Under Climate of Multan (Plant Bulletin, 2023)
Nitrogen use efficiency (NUE) and water scarcity are the biggest problems in the agriculture sector. These problems can arise in arid and semi-arid areas with water scarcity and low soil fertility. Cotton in south Punjab faces these problems during growth and development stages, so the yield results are lower than in other cotton-producing regions. This study was designed to assess the potential of different cotton genotypes grown on various water and nitrogen (N) applications. This study involves seven cotton crop genotypes with three irrigation levels, i.e., 18, 13, and 9 irrigations with N application at 200, 250, and 300 kg ha-1 under randomized complete block design (RCBD) factorial arrangement with three replications of each treatment. The data regarding plant growth, yield, and physiology was collected. The results indicated that Genotype IUB-13 showed a higher N uptake of 0.84% among the other seven genotypes tested at (T2). Among the seven genotypes tested, NAIB-878 demonstrated a significantly higher value of lint weight 1200 g in block-1 and T2.  The finding of this study concluded that higher N levels under deficit irrigation could help to reduce the yield gaps by increasing the growth of cotton genotypes under the climatic conditions of Multan.
Keywords: water scarcity; nitrogen use efficiency; climate change; greenhouse gas emission; cotton